Exploring Tick-Borne Encephalitis Virus-Host Cell Interactions Using Electron Tomography: Methodologies and Protocols - Vancová, Marie; Bílý, Tomáš; Palus, Martin; Růžek, Daniel (Methods in molecular biology (Clifton, N.J.), 2025)
Electron microscopy stands as a cornerstone in unraveling the intricate dynamics of viral infections, with its high-resolution capabilities offering invaluable insights into the interactions between viruses and the infected cells. Here, we present a comprehensive methodology designed to explore the three-dimensional interactions specifically between tick-borne encephalitis virus (TBEV) and host cells. This approach allows to study all stages of viral lifecycle, including replication, budding, maturation, and host cell defense mechanisms. The methodology encompasses a range of techniques, commencing with sample preparation using high-pressure freezing, followed by freeze substitution, epoxy embedding, and ultrathin sectioning. Subsequently, we employ electron tomography in conjunction with image processing and analysis techniques to unravel the intricate nuances of TBEV-host cell interactions.
Keywords: mrazová substituce; Host-Pathogen Interactions; Cell Line; Transmission electron microscopy; replikace viru; Encephalitis Viruses, Tick-Borne; Electron Microscope Tomography; Encephalitis, Tick-Borne; Animals; lidé; Virus Replication; interakce hostitele a patogenu; Humans; Electron tomography; zvířata; klíšťová encefalitida; Freeze Substitution; Tick-borne encephalitis virus; buněčné linie; tomografie elektronová; viry klíšťové encefalitidy